2009
DOI: 10.1534/genetics.109.104695
|View full text |Cite
|
Sign up to set email alerts
|

Fork Stalling and Template Switching As a Mechanism for Polyalanine Tract Expansion Affecting the DYC Mutant of HOXD13, a New Murine Model of Synpolydactyly

Abstract: Polyalanine expansion diseases are proposed to result from unequal crossover of sister chromatids that increases the number of repeats. In this report we suggest an alternative mechanism we put forward while we investigated a new spontaneous mutant that we named ''Dyc'' for ''Digit in Y and Carpe'' phenotype. Phenotypic analysis revealed an abnormal limb patterning similar to that of the human inherited congenital disease synpolydactyly (SPD) and to the mouse mutant model Spdh. Both human SPD and mouse Spdh mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In polyalanine expansion diseases, in which the coding trinucleotide tracts are short and often interrupted, pedigree analyses support the occurrence of both fork stalling and template switching, triggered by secondary structure formation (Fig. 5D), as well as unequal crossing-over between two normal alleles [Arai et al, 2010; Cocquempot et al, 2009; Messaed and Rouleau, 2009; Warren, 1997] (Fig. 5E).…”
Section: Microsatellite Mutationmentioning
confidence: 82%
“…In polyalanine expansion diseases, in which the coding trinucleotide tracts are short and often interrupted, pedigree analyses support the occurrence of both fork stalling and template switching, triggered by secondary structure formation (Fig. 5D), as well as unequal crossing-over between two normal alleles [Arai et al, 2010; Cocquempot et al, 2009; Messaed and Rouleau, 2009; Warren, 1997] (Fig. 5E).…”
Section: Microsatellite Mutationmentioning
confidence: 82%
“…In humans, a growing cohort of neurodegenerative diseases has been attributed to DNA instability at microsatellite DNA noncanonical structures (3,4,7,(11)(12)(13)(14)(15)(16)(17)(18). Thus, replication fork barriers are believed to provoke fork stalling and template switching (FoSTeS), and microhomology-mediated break induced replication (MMBIR) (19)(20)(21)(22)(23)(24)(25)(26). The induction of gross chromosomal rearrangements (GCRs) due to FoSTeS/MMBIR has been implicated in the etiology of several developmental disorders including blepharophimosis syndrome (MIM# 110100) (23), CHARGE syndrome (MIM#214800) (27), and Pelizaeus-Merzbacher disease (MIM#312080) (28).…”
Section: Introductionmentioning
confidence: 99%
“…By replication slippage, both expansions and contractions could occur, depending on whether template or nascent strand misalignment was involved [Strand et al, ; Chen et al, ; McMurray, ]. Finally, Cocquempot et al [] suggested FosTES ( Fo rk s talling and TE mplate S witching) [Lee et al, ] as the mechanism for polyalanine expansion in the Hoxd13 gene in the mouse mutant Dyc , whose structure is quite different from typical HOXA13 or HOXD13 polyalanine expansions. The authors stated that polyalanine tracts contain microhomology, symmetry, and specific sequence motifs that commonly lead to FosTES.…”
Section: Discussionmentioning
confidence: 99%